2012
DOI: 10.1177/1753944712459593
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of nebivolol: does age matter? A retrospective analysis of three randomized, placebo-controlled trials in stage I–II hypertension

Abstract: Abstract:Objectives: This retrospective analysis examined the efficacy and tolerability of nebivolol, a ß 1 -selective, vasodilatory β-blocker, in four different age groups of patients with hypertension. Methods: Data were pooled from three 12-week, randomized, placebo-controlled trials (placebo, n = 205; nebivolol [1.25-30/40 mg/day], n = 1811) and stratified into age quartiles (Group 1: 22-46 years; Group 2: 47-53 years; Group 3: 54-62 years; Group 4: 63-84 years). Only patients treated with placebo and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Our efficacy results are generally in agreement with findings of the age‐stratified pooled analysis of 3 pivotal nebivolol trials (N=1585) and a German observational study (N=5031), which both showed efficacy of nebivolol across the entire age spectrum of adulthood. In the German study, a stronger effect for both DBP and SBP was observed among younger patients (younger than 59 years) vs older patients, and, in the pooled analysis, a significant effect on SBP in the oldest group (63–84 years) was observed only with the dosage of 20 mg/d . However, the extent to which our trial can be compared with those two studies is limited: The German study and the 3 pooled pivotal studies were all fixed‐dose trials, plus the German study was open‐label, with a majority of patients taking other antihypertensives .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our efficacy results are generally in agreement with findings of the age‐stratified pooled analysis of 3 pivotal nebivolol trials (N=1585) and a German observational study (N=5031), which both showed efficacy of nebivolol across the entire age spectrum of adulthood. In the German study, a stronger effect for both DBP and SBP was observed among younger patients (younger than 59 years) vs older patients, and, in the pooled analysis, a significant effect on SBP in the oldest group (63–84 years) was observed only with the dosage of 20 mg/d . However, the extent to which our trial can be compared with those two studies is limited: The German study and the 3 pooled pivotal studies were all fixed‐dose trials, plus the German study was open‐label, with a majority of patients taking other antihypertensives .…”
Section: Discussionsupporting
confidence: 89%
“…The placebo‐subtracted DBP and SBP reductions in our trial were similar to those seen in pivotal, fixed‐dose trials of nebivolol, in which participants' mean age was 54 years . Our efficacy results are generally in agreement with findings of the age‐stratified pooled analysis of 3 pivotal nebivolol trials (N=1585) and a German observational study (N=5031), which both showed efficacy of nebivolol across the entire age spectrum of adulthood. In the German study, a stronger effect for both DBP and SBP was observed among younger patients (younger than 59 years) vs older patients, and, in the pooled analysis, a significant effect on SBP in the oldest group (63–84 years) was observed only with the dosage of 20 mg/d .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results support the notion that effective BP reduction with a combination of a β‐blocker and a RAAS inhibitor may depend on the particular drugs combined. In multiple studies, both nebivolol and valsartan monotherapies have been shown to be safe and effective in patients with hypertension, including in populations susceptible to treatment‐resistant hypertension (eg, elderly, black) . This analysis of the additivity of the nebivolol/valsartan SPCs compared with other approved SPCs for the treatment of hypertension further supports its clinical utility.…”
Section: Discussionmentioning
confidence: 78%
“…in the subgroup analysis [41] and especially beneficial in the group of young patients [42], a special target for the incidence of adrenergic hypertension.…”
Section: Beta-blockers In High Blood Pressure (Hbp)mentioning
confidence: 99%